Towards the sustainable development of logistics system model: A system dynamics approach. - Xuehua Ji; Yue Zhai; Shaochuan Fu; Changxiang Lu (PLoS ONE, 2023)
The contradiction between the limited service capacity of system and the explosive growth of demand has hampered the sustainable development of logistics system. Taking into account the structure of logistics system, this study introduces a system dynamics approach to explore the complex correlation and coupling structure of system, analyzes the multiple feedback loops and design the different scenarios. Results show that the validity and rationality of logistics system model, and the error percentage of GDP and logistics demand factors less than 6%. The influence of the investment in reverse logistics, logistics management, information and organizational management factor on the service quality of logistics system increases in turn. Additionally, adjustment of industrial structure has a significant impact on the investment in information management factor, and highway transportation plays a key role in influencing logistics energy consumption and carbon emissions indexes. The findings can provide valuable references and methodologies, as well as support for decision-making in the sustainable development of logistics system.